Hospitalizations within 14 days of vaccination among pediatric recipients of the live attenuated influenza vaccine, United States 2010–2012. Issue 4 (23rd January 2017) - Millman, Alexander J.; Reynolds, Sue; Duffy, Jonathan; Chen, Jufu; Gargiullo, Paul; Fry, Alicia M.
Abstract: Background: Live attenuated influenza vaccine (LAIV) is safe in healthy children ⩾2 years. The original clinical trials excluded individuals with underlying conditions; however, post-marketing data suggest LAIV may be safe for these populations. Methods: We analyzed MarketScan Commercial Claims Databases from 2010 to 2012 to describe hospitalizations within 14 days of vaccination among LAIV recipients. We evaluated LAIV recipients aged 2–18 years and defined underlying conditions by presence of inpatient or outpatient ICD-9 code during the previous calendar year. We excluded asthma and immunocompromising conditions. We defined risk windows as 1–7 days and 8–14 days after vaccination; the control period was 12–4 days prior to and 15–23 days after vaccination. We conducted a self-controlled case series analysis using a conditional Poisson regression model to estimate incidence-rate ratios (IRR). Results: 1, 216, 123 children aged 2–18 years received LAIV from 2010 to 2012. 634 children met our inclusion criteria and were hospitalized during the observation period (12 days prior to vaccination to 23 days after vaccination). Of those hospitalized, 72 (11.4%) had non-asthma, non-immunocompromising underlying conditions. Children with non-asthma, non-immunocompromising underlying conditions had an all-cause hospitalization IRR of 1.1 (95% CI 0.6–2.0, p = 0.83) in the 1–7 day risk period and 0.9 (95% CI 0.4–1.7, p = 0.67) in the 8–14 day risk period. Children with no underlying conditions had an all-cause hospitalization IRR of 0.9 (0.8–1.2, p = 0.60) in the 1–7 day risk period and 1.1 (95% CI 0.9–1.3, p = 0.53) in the 8–14 day risk period. There were no differences in all-cause hospitalization risk in individuals with non-asthma, non-immunocompromising underlying conditions compared to those without underlying conditions in the 1–7 day (p = 0.88) or 8–14 day (p = 0.24) risk period. Conclusions: We found no evidence of differences in post-LAIV hospitalization risk among children with non-asthma, non-immunocompromising underlying conditions compared to healthy children.